Características clínicas y epidemiológicas de fracturas mandibulares en pacientes atendidos en el Hospital Regional de Loreto 2015-2022 - Cadenas García, Ludwing Ashley (2024)
The objective of this final report was to identify the clinical and epidemiological characteristics of mandibular fractures in patients treated at the Loreto Regional Hospital 2015-2022, where we worked under a quantitative approach with a non-experimental design and descriptive level; opting for a sample of 319 patients, to whom an observation form was used to collect information. According to the results obtained, they demonstrate that the location of the fracture in the patients treated is in the mandibular body; and the type of fractures they present are simple; being a causal agent for falls and traffic accidents; The radiographic examinations are by TEM and frontal skull X-ray; Finally, the associated injuries are due to Edema and lacerations.